Evaluation of Value Engineering Potential in Work Methods and Design of the Primary Canal in the Post-Disaster Gumbasa Irrigation Project - Abdullah Khoir Muhamaddan; Ervina Ahyudanari (Publikasi Indonesia, 2025)
Post-disaster infrastructure reconstruction presents unique challenges, requiring adaptive construction methodologies to address altered geological conditions and optimize resource utilization. The reconstruction work of the Gumbasa irrigation system after the earthquake, tsunami, and liquefaction disasters experienced obstacles in the implementation of the primary channel due to sandy soil conditions that are prone to landslides. The initial design, using precast shoes, was delayed and over budget due to difficulties during field installation. This study applies the value engineering method to evaluate the potential for cost savings and functional improvements through the analysis of work methods and primary channel design. Quantitative and qualitative approaches are used, with stages including information gathering, function analysis, creative ideation, evaluation, and recommendations. The results showed that the cast-in-situ method was superior, achieving a total cost efficiency of IDR 1,062,223,159, or 1.4% of the initial budget. In the lining shoe item, the savings reached IDR 3,397,623,506, or 29.7% of the initial work value. The project duration decreased from 456 days to 240 days, with a time saving of 216 days, or 47.4%. Evaluation of Value Engineering Potential in Work Methods and Design of the Primary Canal in the Post-Disaster Gumbasa Irrigation Project has proven to be effective in assessing post-disaster infrastructure implementation by providing added value in terms of cost, quality, and time.